ASSESSMENT OF THE INVESTMENT RISKS IN THE RUSSIAN UTILITIES INFRASTRUCTURE - O. Temnaya; E. Tregubova (Вестник университета)
The investment risk evaluation technique for water and sanitation sector in the Russian Federation has been proposed. A review of current legislation revealed that there is no holistic approach to investment risk evaluation for Russian Public-Private Partnership projects in domestic utility sector. The article reveals, that various methods can be used for investment risk evaluation (decision tree, effective percentage rate correction, cost sensitivity analysis and others). The method choice is defined according to the type of investment project, the risk evaluation goal, the available information and the type of the identified investment risk. The proposed investment risk evaluation technique takes due account of Russian utility sector investment projects features and the list of disclosed information.